A new species of Parabeloniscus (Opiliones: Laniatores: Epedanidae) from China - Zhang, Chao; Zhang, Feng (Zootaxa, 2012)
The genus Parabeloniscus Suzuki, 1967, which was originally unique to Japan, is newly recorded from China by a newspecies: Parabeloniscus corneus sp. nov., collected from leaf litter in Wuyi Mountain, Fujian Province, China. The newspecies is diagnosed among other characteristics by the free tergite II with a single lateral spine on each side; the free terg-ite III with a remarkable median spine; the femur, patella, tibia and metatarsus of leg IV with conspicuous rows of spines in male; and the penis with a horny stylus.